C.2 - Shackle, G.L.S. (Cambridge, 1959)
The language and theory of economics is very much a part of our lives; yet most of us know little of the meaning of 'inflation', 'productivity' or 'balance of payments', or of the workings of the bank rate or a national monetary policy. The problem is to bridge the gulf between the economist on the one side and the businessman, the banker, the politician, the journalist and the ordinary man on the other. Professor Shackle has provided the solution. In his book the first part of each chapter presents a familiar situation typifying some aspects of economic theory, the second comments on it and introduces and explains the relevant technical terms. This 1968 edition has two additional chapters: one on input-output analysis and activity analysis, the other giving an account of the theory of growth originated by Sir Roy Harrod.
Keywords: Economics